2014
DOI: 10.3991/ijes.v2i4.4016
|View full text |Cite
|
Sign up to set email alerts
|

ICTs in English Learning and Teaching

Abstract: A great number of articles have been written about English language teaching and the use of ICTs (Information and Communication Technologies) during the last decade, achieving a laudable outcome. Recent literature has shown that the use of ICTs in the language classroom has a lot to offer to both learners and teachers, with learners enhancing their vocabulary, improving their reading and speaking skills, and with teachers having to hold a double role; the role of the educator and that of the facilitator, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
(33 reference statements)
1
17
0
1
Order By: Relevance
“…Students are normally eager to use their mobile phones or tablets and implement technology into the classroom. These applications provide a positive environment in the classroom, increase energy and add enjoyable moments in learning (Drigas & Charami, 2014). Kahoot!…”
Section: Discussionmentioning
confidence: 99%
“…Students are normally eager to use their mobile phones or tablets and implement technology into the classroom. These applications provide a positive environment in the classroom, increase energy and add enjoyable moments in learning (Drigas & Charami, 2014). Kahoot!…”
Section: Discussionmentioning
confidence: 99%
“…Pemanfaatan teknologi dan media berbasis TIK dalam pembelajaran dipercaya dapat memberikan banyak manfaat dan efek positif (Ghasemi & Hashemi, 2011;Khanom, 2018). Seperti halnya yang sudah dikemukakan oleh banyak peneliti, implementasi pemanfaatan teknologi yang efektif dapat meningkatkan Jurnal Penelitian Pendidikan ISSN 1412-565 X e-ISSN 2541 motivasi siswa dalam belajar, memungkinkan siswa untuk melihat simulasi kontak langsung dengan kebudayaan dan negara penutur bahasa Inggris, menyediakan akses untuk menjangkau sumber materi dari seluruh dunia, memfasilitasi pembelajaran untuk siswa dalam berbagai gaya belajar dan stategi belajar, atau bahkan bisa meningkatkan otonomi pembelajar, menajamkan pemikiran kritis siswa, dan juga dapat menjadi sebuah proses yang dapat dijadikan solusi untuk berbagai masalah dalam belajar dan pembelajaran (Almunawwarah, 2014;Drigas & Charami, 2014;Ghasemi & Hashemi, 2011;Khanom, 2018;Shyamlee et al, 2012). Akan tetapi, praktik guru dalam pemanfaatan teknologi belum diteliti lebih jauh dalam hal faktor-faktor yang mempengaruhi praktik guru dalam pemanfaatan teknologi di dalam kelas.…”
Section: Pendahuluanunclassified
“…Some prior studies on ICT in educational settings have shown that ICT has been able to develop teaching and learning in a more efficient manner [11]. In the context of language learning, ICT has enabled learners to acquire their language skills as ICT can mediate learners to communicate with others around the world [12]. In addition, the use of ICT in the classroom could improve the skills of the twenty-firstcentury students, particularly in their critical thinking, problem-solving, communication, and collaboration ( [13], [14]).…”
Section: A Ict and The 21st-century Skills Of High School Studentsmentioning
confidence: 99%